Predictors for Quality of Life and General Health Perceptions - A Prospective Cohort Study in Breast Cancer Survivors - Eneberg, Pauliina (My University, 2023)
Background: Factors that are related to the long-term Health-related Quality of Life (HrQoL) in breast cancer survivors are not well understood. This study aimed to identify predictors for two important HrQoL outcomes, General Health Perceptions (GHP) and Quality of Life (QoL) in a large, prospective cohort study. Theoretical background based on the Conceptual Model for Health-related Quality of Life (Ferrans, et al., 2005). Methods: Women with unilateral, non-metastasized breast cancer were followed up to 5.5 years after the surgery. 715 women participated to the last follow up, and 631 were included to the final analysis (age 36-81 yrs). Multivariable hierarchical linear regression analysis was used to assess whether depressive symptoms, trait anxiety, menopausal symptoms, and insomnia measured 12 months after the surgery predicted GHP and QoL four and half years later. The role of preoperative chronical pains, treatment modalities and sociodemographic factors were also explored. Younger and older half of the cohort (median age 12 months after the surgery = 59 years) were analysed separately to assess possible age group dependent effects. Results: Higher trait anxiety, menopausal symptoms, presence of preoperative chronic pain, (severe) insomnia, higher body mass index, axillary lymph node dissection and absence of chemotherapy predicted worse GHP in the whole cohort, R2 Adj. = .219, F(8,504) = 18.996, p < .001. Higher depressive symptoms, menopausal symptoms and higher body mass index predicted poor QoL, R2 Adj. = .205, F(3,527) = 46.573, p < .001. Determinants were partly age group dependent, as menopausal symptoms predicted worse outcomes only in older age group whereas insomnia was relevant only predicting GHP among younger women. Depressive symptoms alone were the major determinant for QoL, explaining 12 % of QoL variance in the younger age group and 24.5 % in the older age group. Conclusion: Symptom level predictors and especially psychological factors are the major determinant for long-term GHP and QoL in breast cancer survivors. Treatment modalities or sociodemographic factors are not likely to be the key in finding those at high risk for poor long-term HrQoL. Age group specific approaches are needed in order to identify vulnerable survivors, and more attention should be given especially to those older women who report depressive symptoms. Effective symptom management during the first year after the breast cancer diagnosis is likely the most promising possibility to prevent long-term impairments.

Rintasyöpään sairastuneen elämänlaatua ja koettua terveydentilaa selittävät tekijät – prospektiivinen 5.5 vuoden kohorttitutkimus Tausta: Tekijöitä, jotka selittävät rintasyöpään sairastuneen terveyteen liittyvää elämänlaatua pitkällä aikavälillä tunnetaan edelleen huonosti. Tässä tutkimuksessa tarkoituksena oli tunnistaa mikä selittää koettua terveydentilaa ja elämänlaatua pitkällä aikavälillä suuressa kohorttitutkimuksessa. Tutkimuksen teoriatausta nojautui Ferransin ja kumppaneiden (2005) konseptuaaliseen malliin. Menetelmät: Tutkimuksessa seurattiin rintasyöpää sairastaneita naisia 5.5. vuoden ajan leikkauksen jälkeen. Viimeiseen seurantaan osallistui 715 naista, joista 631 sisällytettiin lopulliseen analyysin. Naiset olivat iältään 36–81-vuotiaita. Analyysimenetelmänä käytettiin usean selittäjän lineaarista regressioanalyysia, jonka avulla tarkasteltiin missä määrin masennusoireet, piirreahdistuneisuus, vaihdevuosioireet ja unettomuus 12 kk leikkauksen jälkeen selittävät koettua terveydentilaa ja elämänlaatua neljä ja puoli vuotta myöhemmin. Myös aikaisen kroonisen kivun, hoitomuodon ja sosiodemografisten tekijöiden merkitystä tutkittiin. Ikäryhmäriippuvaisia selittäjiä tutkittiin analysoimalla selittäjiä erikseen kohortin nuoremmalle ja vanhemmalle puolikkaalle. Tulokset: Piirreahdistuneisuus, vaihdevuosioireet, aikaiset krooniset kivut, (vakava) unettomuus, suurempi painoindeksi, imusolmukkeiden kainaloevakuaatio ja hoito, johon ei kuulunut kemoterapiaa ennusti alhaisempaa koettua terveydentilaa, R2 Adj. = .219, F(8,504) = 18.996, p < .001. Masennus- ja vaihdevuosioireet sekä suurempi painoindeksi selittivät alhaista elämänlaatua, R2 Adj. = .205, F(3,527) = 46.573, p < .001. Päätemuuttujia selittävät tekijät olivat osin ikäryhmäriippuvaisia, ja varsinkin vanhemmassa ryhmässä masennusoireet selittivät huomattavan osan, 24.5 %, elämänlaadun vaihtelusta. Johtopäätökset: Varhaisen vaiheen oiretaso ja erityisesti psykologiset tekijät selittävät merkittävissä määrin koettua terveydentilaa ja elämänlaatua pitkällä aikavälillä. Näihin verrattuna hoitomuodon ja sosiodemografisten tekijöiden merkitys on vähäinen. Ikäryhmästä riippuvaiset lähestymistavat ovat tarpeen riskipotilaiden tunnistamiseksi ja etenkin vanhempien ikäryhmien osalta masennusoireiluun tulee kiinnittää enemmän huomiota. Tehokas oireiden hoitaminen ja erityisesti psyykkisen oireilun huomioinen ensimmäisen vuoden aikana vaikuttaa lupaavimmalta mahdollisuudelta vaikuttaa myös pitkän aikavälin hoitotuloksiin ja rintasyöpäselviytyjien elämänlaatuun.
Keywords: Quality of Life, General Health Perceptions, Breast Cancer Survivors, Long-term Survivors, Depression, Trait Anxiety, Insomnia, Menopausal Symptoms, Preoperative Chronic Pain